Assessing System Accuracy of Blood Glucose Monitoring Systems Using Rectangle Target Plots. (March 2016) - Müller, Peter; Hattemer, Andrew; Stephan, Peter
Background: Results from accuracy assessments of systems for self-monitoring of blood glucose (SMBG) are often visualized in difference or regression plots. These approaches become more difficult to read as the number of data points displayed increases, thus limiting their use. In the recently presented rectangle target plot (RTP) approach, data from each reagent system lot or product are displayed graphically as a single rectangle, thus allowing the plot to remain comprehensible even when displaying system accuracy data from multiple reagent system lots or products. Methods: The RTP illustrates the accuracy of SMBG systems. Each rectangle shows the mean bias and the variability of a system. By use of statistical tolerance intervals, each rectangle most closely approximates the total error for lower (<100 mg/dL) and upper (≥100 mg/dL) glucose concentrations. RTPs were created for data from 8 different manufacturers of systems for SMBG. In total, the accuracy data of 87 different reagent system lots of 50 different SMBG systems were displayed in RTPs. Results: The RTP approach was suitable for 81 of the 87 reagent system lots analyzed. In the remaining cases, outliers caused excessive skewness of the distribution of measurements. The reagent system lots analyzed were grouped according to manufacturer in RTPs. Data from 3 to 15 different reagent system lots were displayed in each RTP. Conclusion: Applying the RTP approach to a large number of reagent system lots showed that it was suitable in more than 93% of cases analyzed. The display of system accuracy data in RTPs enables lot-to-lot variability within specific products and product reliability of specific manufacturers to be visualized in a comprehensible manner.